Effect of in-situ moisture conservation practices and integrated nutrient management on nutrient availability and grain yield of rabi sorghum (Sorghum bicolor) in the Vertisols of semi-arid tropics of south India - PATIL, S L; SHEELAVANTAR, M N (The Indian Journal of Agricultural Sciences, 2014)
A study was conducted during 1994-96 at Bijapur on the effect of in-situ moisture conservation practices and integrated use of organic and inorganic sources of nutrients on crop yield and soil properties. Compartmental bunding and ridges and furrows increased the grain yield by 22.8 and 25.6 % respectively. mainly owing to reduction in runoff, soil loss and increased availability of moisture and nutrients. viz N. P and K. Higher availability of nutrients in the top soil (0-15 em depth) compared to sub soil (15-30 em depth) was due to application of nutrients and higher rate of mineralisation. Among different sources of organics, application of white popinac (Leucaena leucocephala Lam.) proved superior over farmyard manure and vermicompost due to higher moisture conservation and faster rate of mineralisation and higher nutrient availability. Increase in N dose up to 50 kg/ha increased the availability of nutrients and their uptake resulted in improved crop growth and grain yield over 2S kg/ha and control.